Baicalin Ameliorates Cognitive Impairment and Protects Microglia from LPS-Induced Neuroinflammation via the SIRT1/HMGB1 Pathway. (22nd September 2020) - Li, Yue; Liu, Taotao; Li, Yitong; Han, Dengyang; Hong, Jingshu; Yang, Ning; He, Jindan; Peng, Ronghui; Mi, Xinning; Kuang, Chongshen; Zhou, Yang; Han, Yongzheng; et al.
Abstract : Systemic inflammation often induces neuroinflammation and disrupts neural functions, ultimately causing cognitive impairment. Furthermore, neuronal inflammation is the key cause of many neurological conditions. It is particularly important to develop effective neuroprotectants to prevent and control inflammatory brain diseases. Baicalin (BAI) has a wide variety of potent neuroprotective and cognitive enhancement properties in various models of neuronal injury through antioxidation, anti-inflammation, anti-apoptosis, and stimulating neurogenesis. Nevertheless, it remains unclear whether BAI can resolve neuroinflammation and cognitive decline triggered by systemic or distant inflammatory processes. In the present study, intraperitoneal lipopolysaccharide (LPS) administration was used to establish neuroinflammation to evaluate the potential neuroprotective and anti-inflammatory effects of BAI. Here, we report that BAI activated silent information regulator 1 (SIRT1) to deacetylate high-mobility group box 1 (HMGB1) protein in response to acute LPS-induced neuroinflammation and cognitive deficits. Furthermore, we demonstrated the anti-inflammatory and cognitive enhancement effects and the underlying molecular mechanisms of BAI in modulating microglial activation and systemic cytokine production, including tumor necrosis factor- (TNF-) α and interleukin- (IL-) 1 β, after LPS exposure in mice and in the microglial cell line, BV2. In the hippocampus, BAI not only reduced reactive microglia and inflammatory cytokine production but also modulated SIRT1/HMGB1 signaling in microglia. Interestingly, pretreatment with SIRT1 inhibitor EX-527 abolished the beneficial effects of BAI against LPS exposure. Specifically, BAI treatment inhibited HMGB1 release via the SIRT1/HMGB1 pathway and reduced the nuclear translocation of HMGB1 in LPS-induced BV2 cells. These effects were reversed in BV2 cells by silencing endogenous SIRT1 . Taken together, these findings indicated that BAI reduced microglia-associated neuroinflammation and improved acute neurocognitive deficits in LPS-induced mice via SIRT1-dependent downregulation of HMGB1, suggesting a possible novel protection against acute neurobehavioral deficits, such as delayed neurocognitive recovery after anesthesia and surgery challenges.